INTERPOL AS A MECHANISM OF INTERNATIONAL POLICE COOPERATION: LEGAL FRAMEWORK, TOOLS, AND PRACTICAL EFFECTIVENESS - Aliyeva A. B. (Modern American Journals, 2025)
This article examines the activities of the International Criminal Police Organization (INTERPOL) as a key mechanism of international police cooperation in the context of growing transnational crime. It analyzes the legal foundations of INTERPOL’s functioning, its organizational structure, system of notices, and the role of National Central Bureaus. Particular attention is paid to the principles of political neutrality, the protection of human rights in the process of international investigations, and the effectiveness of cooperation with national law enforcement agencies. Using the experience of the Republic of Uzbekistan as an example, the study identifies directions for improving INTERPOL’s operations and strengthening international security.
Keywords: INTERPOL; international police cooperation; notices; transnational crime; legal status.